Anti-Corruption Education Workshop as an Early Anti-Corruption Outreach Program for Early Childhood Educators - Ardina, Mona; Wahyuni, Desvi; Indrawati, Indrawati (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2025)
Background: The study addresses the lack of understanding among teachers regarding the values of anti-corruption education implemented in schools. This is evident from the minimal knowledge of teachers regarding acts of corruption normalized in educational environments, especially in early childhood education (ECE).Aims: The objective of this community service activity is to disseminate anti-corruption values, which are often normalized in educational settings.Methods: The methods used in this activity were workshops and evaluations of teachers' knowledge of anti-corruption values, which are often conducted in early childhood education settings.Results: The findings showed that early childhood teachers at TKIT Baitul Izzah have taught anti-corruption values through daily activities, although in practice there are still some activities that are considered normal, such as accepting gifts from parents. This is due to the belief that gifts from others, including parents, should not be refused. As for the teachers' understanding after participating in the community service program, it increased from 41.8% to 86.5%.Conclusion: These results show that teachers' understanding of anti-corruption education values has begun to improve, as evidenced by the awareness demonstrated by teachers after participating in the outreach activities.